Genetic associations of human leukocyte antigen alleles in cutaneous delayed drug hypersensitivity reactions: An updated review - Chun-Bing Chen; Chih-Chun Lee; Chuang-Wei Wang; Wei-Kai Hung (Wolters Kluwer Medknow Publications, 2023)
Cutaneous delayed drug hypersensitivity reactions (DHRs) are common iatrogenic events with potentially life-threatening consequences. Delayed DHRs encompass diverse phenotypes and can be classified by their distinct T-cell responses to drug antigens. Interaction between the immune receptors, human leukocyte antigen (HLA) and T-cell receptor (TCR), and the complementary antigenic peptide is required for the development of delayed DHRs. These idiosyncratic interactions can be elicited by the formation of antigenic drug-protein adducts (hapten hypothesis) or from direct interactions of drugs with the immune receptors (pharmacological interaction of drugs with immune receptors concept, altered peptide repertoire model, and altered TCR model). In addition, viral infections may play a role by providing co-stimulatory signals or enhancing TCR/HLA expression on T-cells. The associations of HLA allele polymorphisms and DHRs are phenotype and ethnicityspecific. The discovery of genetic polymorphisms associated with DHRs has provided a strategy to prevent and diagnose potentially life-threatening reactions. Recently, advances in next-generation sequencing technologies, such as the incorporation of whole-exome or whole-genome sequencing, enabled the comprehensive detection of susceptibility loci. Several HLA associations have shown clinical utility and cost-effectiveness, such as HLA-B*15:02 (carbamazepine-induced Stevens-Johnson syndrome/toxic epidermal necrolysis in Han Chinese), HLA-B*58:01 (allopurinol-induced severe cutaneous adverse reactions in Han Chinese), HLA-B*57:01 (abacavir hypersensitivity reactions in Caucasians), and HLA-B*13:01 (dapsone-induced drug reaction with eosinophilia and systemic symptoms in Han Chinese). Herein, we summarize the current knowledge of the pathogenesis, antigen presentation models, and HLA associations of cutaneous delayed DHRs.